1998
DOI: 10.1095/biolreprod59.4.836
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in the Expression of the Growth Hormone Receptor Messenger Ribonucleic Acid and Protein in the Bovine Ovary1

Abstract: By reverse transcription-polymerase chain reaction, the transcript of the growth hormone receptor (GHR) was demonstrated in oocytes, follicular cells, and corpus luteum of the bovine ovary. Immunoblotting using the monoclonal antibody mAb 263 resulted in a distinct protein band at 120 kDa, confirming that translation of the mRNA takes place in the same cells. Nonradioactive in situ hybridization revealed that distribution of the mRNA encoding GHR was correlated with the developmental stage of the follicle. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 36 publications
6
51
1
4
Order By: Relevance
“…Cleavage rate was evaluated on day-2 post insemination. maturation [7,12,17]. Moreover, GH stimulates in vitro oocyte maturation as well as embryo development in cattle [3][4][5].…”
Section: Methodsmentioning
confidence: 99%
“…Cleavage rate was evaluated on day-2 post insemination. maturation [7,12,17]. Moreover, GH stimulates in vitro oocyte maturation as well as embryo development in cattle [3][4][5].…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of RA, the growth hormone (GH) receptor (GHr) gene increases transcription (Ohlsson et al 1993, Slootweg et al 1996. The transcript of the GHr was demonstrated in oocytes, follicular cells and the corpus luteum of the bovine ovary (Kolle et al 1998), and GH was found to stimulate the bovine oocyte during IVM via cumulus cells (Izadyar et al 1997, Kolle et al 2003.…”
Section: Embryos Transferred Pregnancy (%)mentioning
confidence: 99%
“…Receptores de somatotropina e IGF-1 têm sido encontrados em oócitos bovinos imaturos e nas células da granulosa e do cumulus Spicer & Stewart, 1996;Izadyar et al, 1997;Kölle et al, 1998;Yoshida et al, 1998;Lonergan et al, 2000). A adição de rbST (Izadyar et al, 1997(Izadyar et al, , 1998) ou IGF-1 (Herrler et al, 1992;Markkula & Makarevich, 2001) ao meio de maturação in vitro tem aumentado o número de mórulas e de blastocistos.…”
Section: Resultsunclassified